Additions to Philippine Slender Skinks of the Brachymeles bonitae Complex (Reptilia: Squamata: Scincidae) I: a new species from Lubang Island - Geheber, Aaron D.; Davis, Drew R.; Watters, Jessa L.; Penrod, Michelle L.; Feller, Kathryn D.; Davey, Conner S.; Ellsworth, Elyse D.; Flanagan, Rachel L.; Heitz, Brendan B.; Moore, Tana; Nguyen, Marie D. C.; Roberts, Austyn; et al. (Zootaxa, 2016)
A new species of slender skink is described from the Philippines. The species is endemic to Lubang Island, and is assigned to the Brachymeles bonitae Complex based on phenotypic and genetic data. Specimens were collected from Lubang Island between 1991 and 2012, and were examined based on morphological data (qualitative traits, meristic counts, and mensural measurements). Published genetic sequence data from phylogenetic studies of the genus reveal the new species to be highly divergent from congeners. Brachymeles ligtas sp. nov. is differentiated from other members of the genus based on a number of distinct morphological features, including small body size (SVL 60.7–79.6 mm), bidactyl fore-limbs, digitless hind limbs, high number of presacral vertebrae (50), and the absence of auricular openings. Additionally, the new species has diagnostic, distinct dorsal head scale patterns. This new species becomes the only member of the genus known to occur on the deep-ocean island of Lubang.